Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

The Rotokawa geothermal system, New Zealand: Hydrothermal minerals and punctuated evolution - Mark P. Simpson; Amando G. Morales; Isabelle Chambefort; Samantha Alcaraz; Shunsuke Moribe; Sarah D. Milicich; Fabian Sepulveda; Jeffrey W. Hedenquist (Journal of Volcanology and Geothermal Research, 2026)

Per- and polyfluoroalkyl substances, vitamin D, and risk of preterm birth in a Canadian cohort - Mandy Fisher; James Owen; Leonora Marro; Beth Potter; Hope A. Weiler; Gillian England-Mason; Michael M. Borghese; Mark Walker; Linda Dodds; Michael Helewa; Tye E. Arbuckle; Bruce Lanphear; et al. (Environmental Research, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

The effect of place-based nature interventions on human health: A systematic review - Dustin Fry; Jalayna Antoine; Kylan Simpson; Ava-Clare Steed; Charles C. Branas; Mark Nieuwenhuijsen; Kristin Mmari; Michelle C. Kondo (Environmental Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Temperature-driven plasticity in boldness, its predictability and learning in the beadlet anemone, Actinia equina - Samantha Simpson; Dunia Gonzales; Mark Briffa (Animal Behaviour, 2025)

The Blue Carbon Cost Tool – understanding market potential and investment requirements for high-quality coastal wetland projects - Stefanie Simpson; Lindsey S. Smart; Emily Landis; Stephanie Van Laere; Abu S. M. G. Kibria; Olga Albot; Mark Beeston; Catherine E. Lovelock; Robert I. McDonald; Ryan P. Moyer; Thomas A. Worthington; Tania L. Maxwell; et al. (Frontiers in Marine Science, 2025)
Blue carbon ecosystems, such as mangroves, tidal marshes, and seagrasses, are important for climate mitigation. As carbon sinks, they often exhibit higher per hectare carbon storage capacity and sequestration rates than terrestrial systems. These ecosystems provide additional benefits, including enhancing water quality, sustaining biodiversity, and maintaining coastal resilience to climate change impacts. The widespread loss of blue carbon ecosystems due to anthropogenic activities can contribute to increasing carbon emissions globally. Monetizing blue carbon through carbon credits offers an avenue to generate revenue and incentivize conservation and restoration efforts. However, limited data on project costs and carbon benefits make prioritization of blue carbon projects challenging. To address these challenges, we have developed, in collaboration with blue carbon experts, the Blue Carbon Cost Tool. This is a user-friendly interface enabling comparison of three core market project components – 1) carbon credit estimation, 2) project cost estimation, and 3) a qualitative, non-economic feasibility assessment – to assess and compare potential for blue carbon projects. Tool simulations with data available from nine countries demonstrate (a) how factors such as country, ecosystem type and project scale drive variability, (b) the need for local or project-specific data to enhance accuracy and reduce uncertainty, particularly in tidal marsh and seagrass systems, and (c) that higher price tolerance or upfront capital is needed to bridge implementation and maintenance cost gaps. The Blue Carbon Cost Tool can aid project developers and investors to better understand market opportunity and the resources needed to develop high quality blue carbon market projects.

Calcite priming of a hydrothermal eruption at South Orakonui, Ngā Tamariki Geothermal Field, New Zealand - Mark P. Simpson; Michael D. Rosenberg; Cristian Montanaro; Duncan J. Graham (Journal of Volcanology and Geothermal Research, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Impact of wildfires on sediment quality in estuaries in New South Wales, Australia - Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Mark Farrell; Sally A. Bracewell; Emma L. Johnston (Chemosphere, 2025)

A generalised sigmoid population growth model with energy dependence: Application to quantify the tipping point for Antarctic shallow seabed algae - Elise Mills; Graeme F. Clark; Matthew J. Simpson; Mark Baird; Matthew P. Adams (Environmental Modelling & Software, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

An ocean practices maturity model: from good to best practices - Carlo Mantovani; Jay Pearlman; Anna Rubio; Rachel Przeslawski; Mark Bushnell; Pauline Simpson; Lorenzo Corgnati; Enrique Alvarez; Simone Cosoli; Hugh Roarty (Frontiers in Marine Science, 2024)
Ocean practices, intended as a wide spectrum of methodologies supporting ocean-related research, operations, and applications, are constantly developed and improved to enable informed decision-making. Practices start from the idea of an individual or a group and often evolve towards what can be called good or best practices. This bottom-up approach may in principle result in different paths for the evolution of each practice, and ultimately generate situations where it is not clear to a new user how to compare two practices aiming at the same objective, and determine which one is best. Also, although a best practice is supposed to be the result of a multi-institutional collaborative effort based on the principles of evidence, repeatability and comparability, a set of individual requirements is not yet defined in literature for a practice to be considered a good, better, and ultimately a best practice. This paper proposes a method for addressing those questions and presents a new maturity model for ocean practices, built upon existing maturity models for systems and software, developed and adopted in the last decades. The model provides attributes for assessing both the maturity of the practice description and its implementation. It also provides a framework for analyzing gaps and suggesting actions for practice evolution. The model has been tested against a series of widely adopted practices and the results are reported and discussed. This work facilitates a common approach for developing and assessing practices, from which greater interoperability and trust can be achieved.

Trends and geographic variation in adverse impacts of nitrogen use in Europe on human health, climate, and ecosystems: A review - Wim de Vries; Maximillian Posch; Dave Simpson; Frank A.A.M. de Leeuw; Hans J.M. van Grinsven; Lena F. Schulte-Uebbing; Mark A. Sutton; Gerard H. Ros (Earth-Science Reviews, 2024)

Laser ablation (in situ) Lu-Hf geochronology of epidote group minerals - Jie Yu; Stijn Glorie; Martin Hand; Alexander Simpson; Sarah Gilbert; Kristoffer Szilas; Nick Roberts; Mark Pawley; Yanbo Cheng (Contributions to Mineralogy and Petrology, 2024)
Epidote group minerals, including allanite, clinozoisite and epidote are common in a range of metamorphic, igneous and hydrothermal systems, and are stable across a wide range of pressure – temperature ( P–T ) conditions. These minerals can incorporate substantial amounts of rare earth elements (REEs) during their crystallisation, making them potential candidates for Lu–Hf geochronology to provide age constraints on various geological processes. Here we report on a first exploration into the feasibility of in situ Lu–Hf geochronology for epidote group minerals from various geological settings and compare the results with age constraints from other geochronometers. Magmatic allanite samples from pegmatites and monzogranites in the Greenland anorthosite complex, Coompana Province and Qingling Orogen provided dates consistent with magmatic events spanning from c. 2660 to 1171 Ma. In the Qingling pegmatites, a younger phase of hydrothermal allanite was dated at c. 215 Ma, consistent with the timing of regional REE mineralisation. Allanite from the Yambah Shear Zone, Strangways Metamorphic Complex, yielded Lu–Hf age of c. 430 Ma. It predates the garnet and apatite growth at c. 380 Ma, suggesting the Lu–Hf system can be preserved in allanite during prograde amphibolite-facies metamorphism. Additionally, Lu–Hf dates for hydrothermal clinozoisite and epidote are consistent with the timing of hydrothermal alteration and mineralisation in a range of settings, demonstrating the utility of the technique for mineral exploration. Despite the current lack of matrix-matched reference materials, the successful application of laser ablation Lu–Hf geochronology to epidote group minerals offers valuable geochronological insights into various geological processes that can be difficult to access through other geochronometers.

Testing in-situ apatite Lu–Hf dating in polymetamorphic mafic rocks: a case study from Palaeoproterozoic southern Australia - Dillon A. Brown; Anthony Reid; Elizabeth A. Jagodzinski; Megan Williams; Alex Simpson; Mark Pawley; Christopher L. Kirkland; Claire Wade; Alexander T. De Vries Van Leeuwen; Stijn Glorie (Contributions to Mineralogy and Petrology, 2024)
In mafic systems where primary mineral assemblages have witnessed moderate- to high-temperature hydrous overprinting and deformation, little is known about the retentivity of the Lu–Hf isotopic system in apatite. This study presents apatite laser-ablation Lu–Hf and U–Pb geochronology, zircon geochronology, and detailed petrological information from polymetamorphic mafic intrusions located in the central-western Gawler Craton in southern Australia, which records an extensive tectonometamorphic history spanning the Neoarchaean to the Mesoproterozoic. Zircon records magmatic crystallisation ages of c. 2479–2467 Ma, coinciding with the onset of the c. 2475–2410 Ma granulite-facies Sleafordian Orogeny. The amphibole-dominant hydrous assemblages which extensively overprint the primary magmatic assemblages are hypothesised to post-date the Sleafordian Orogeny. The Lu–Hf and U–Pb isotopic systems in apatite are used to test this hypothesis, with both isotopic systems recording significantly younger ages correlating with the c. 1730–1690 Ma Kimban Orogeny and the c. 1590–1575 Ma Hiltaba magmatic event, respectively. While the early Mesoproterozoic apatite U–Pb ages are attributed to thermal re-equilibration, the older Lu–Hf ages are interpreted to reflect re-equilibration facilitated primarily by dissolution-reprecipitation, but also thermally activated volume diffusion. The mechanisms of Lu–Hf isotopic resetting are distinguished based on microscale textures and trace element abundances in apatite and the integration of apatite-amphibole textural relationships and temperatures determined from the Ti content in amphibole. More broadly, the results indicate that at low to moderate temperatures, apatite hosted in mafic rocks is susceptible to complete recrystallisation in rocks that have weak to moderate foliations. In contrast, at higher temperatures in the absence of strain, the Lu–Hf system in apatite is comparatively robust. Ultimately, the findings from this study advance our understanding of the complex role that both metamorphism and deformation play on the ability of mafic-hosted apatite to retain primary Lu–Hf isotopic signatures.

Mitogenomic evidence of population differentiation of thorny skate, Amblyraja radiata , in the North Atlantic - John S. S. Denton; Jeff Kneebone; Lei Yang; Arve Lynghammar; David McElroy; Shannon Corrigan; Klara Jakobsdóttir; Carolyn Miri; Mark Simpson; Gavin J. P. Naylor (Journal of Fish Biology, 2024)
Management of thorny skate ( Amblyraja radiata ) in the Northwest Atlantic has posed a conservation dilemma for several decades due to the species' lack of response to strong conservation efforts in the US Gulf of Maine and the Canadian Scotian Shelf, confusion over the relationship between two reproductive size morphs of differing life histories that are sympatric in the Northwest Atlantic, and conflicting data on regional population connectivity throughout the species' broader range. To better assess potential A. radiata regional population differentiation and genetic links to life‐history variation, we analysed complete mitochondrial genome sequences from 527 specimens collected across the species' North Atlantic geographic range, with particular emphasis on the Northwest Atlantic region. A high level of genetic diversity was evident across the North Atlantic, but significant genetic differentiation was identified between specimens inhabiting the Northwest (Gulf of Maine and Newfoundland) and Northeast (Greenland, Iceland, North Sea, and Arctic Circle) Atlantic. In the Northwest Atlantic, significant differentiation between the Gulf of Maine and Newfoundland regions was revealed; however, the overall level of differentiation was very low. No genetic difference was identified between the large and small reproductive morphs. The results of this study advance our understanding of A. radiata population structure in the North Atlantic but do not resolve all the questions confounding our understanding of the species' biology and evolutionary history.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Distinct coral reef habitat communities characterized by environmental DNA metabarcoding - Laurence Dugal; Luke Thomas; Abinaya Meenakshisundaram; Tiffany Simpson; Rose Lines; Jamie Colquhoun; Simon Jarman; Mark Meekan (Coral Reefs, 2023)
Coral reefs are biodiversity hotspots, places of high endemicity and provide essential services to billions of people globally. With increasing threats to these reefs worldwide, there is a need to implement faster, more efficient ways to monitor spatial and temporal patterns of biodiversity. Environmental DNA (eDNA) metabarcoding offers a promising tool to address this issue, as it has revolutionized our ability to monitor biodiversity from complex environmental samples such as seawater. However, the capacity for eDNA to resolve fine scale shifts in community composition across habitats in seascapes is yet to be fully explored. Here, we applied eDNA metabarcoding using the rRNA 18S Universal eukaryote assay to explore differences in community profiles between samples collected from the lagoon and reef slope habitats across more than 170 km of the Ningaloo Coast World Heritage Area in Western Australia. We recovered 2061 amplicon sequence variants that comprised of 401 taxa spanning 14 different metazoan phyla such as cnidarians, poriferans, molluscs, algae, worms, and echinoderms. Our results revealed strong clustering of samples by habitat type across the length of the reef. Community dissimilarity (beta diversity) between samples collected from the reef slope and lagoon habitats was high and was driven largely by a strong rate of spatial turnover, indicating a distinct set of taxa representing each reef zone community. We also detected a strong pattern of isolation by distance within our slope samples, suggesting that communities are spatially stratified across the length of the reef. Despite high connectivity due to regular flushing of the lagoon environment, our results demonstrate that metabarcoding of seawater eDNA from different habitats can resolve fine scale community structure. By generating multi-trophic biodiversity data, our study also provided baseline data for Ningaloo from which future changes can be assessed.

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Opening Doors to Training Medical Toxicology Fellows from All Residency Backgrounds - Louise Kao; Michele Burns; Christine Murphy; Evan Schwarz; Steve Aks; Kavita Babu; Gillian Beauchamp; Rana Biary; Michele Burns; Nathan Charlton; Cathleen Clancy; Jonathan Ford; et al. (Journal of Medical Toxicology, 2022)

Modelling the effects of cold temperature during the reproductive stage on the yield of chickpea (Cicer arietinum L.) - Muhuddin Rajin Anwar; David J. Luckett; Yashvir S. Chauhan; Ryan H. L. Ip; Lancelot Maphosa; Marja Simpson; Annie Warren; Rosy Raman; Mark F. Richards; Georgina Pengilley; Kristy Hobson; Neroli Graham (International Journal of Biometeorology, 2022)
During the reproductive stage, chilling temperatures and frost reduce the yield of chickpea and limit its adaptation. The adverse effects of chilling temperature and frost in terms of the threshold temperatures, impact of cold duration, and genotype-by-environment-by-management interactions are not well quantified. Crop growth models that predict flowering time and yield under diverse climates can identify combinations of cultivars and sowing time to reduce frost risk in target environments. The Agricultural Production Systems Simulator (APSIM-chickpea) model uses daily temperatures to model basic crop growth but does not include penalties for either frost damage or cold temperatures during flowering and podding stages. Regression analysis overcame this limitation of the model for chickpea crops grown at 95 locations in Australia using 70 years of historic data incorporating three cultivars and three sowing times (early, mid, and late). We modified model parameters to include the effect of soil water on thermal time calculations, which significantly improved the prediction of flowering time. Simulated data, and data from field experiments grown in Australia (2013 to 2019), showed robust predictions for flowering time ( n = 29; R 2 = 0.97), and grain yield ( n = 22; R 2 = 0.63–0.70). In addition, we identified threshold cold temperatures that significantly affected predicted yield, and combinations of locations, variety, and sowing time where the overlap between peak cold temperatures and peak flowering was minimal. Our results showed that frost and/or cold temperature–induced yield losses are a major limitation in some unexpected Australian locations, e.g., inland, subtropical latitudes in Queensland. Intermediate sowing maximise yield, as it avoids cold temperature, late heat, and drought stresses potentially limiting yield in early and late sowing respectively.

Evolving and Sustaining Ocean Best Practices to Enable Interoperability in the UN Decade of Ocean Science for Sustainable Development - Jay Pearlman; Pier Luigi Buttigieg; Mark Bushnell; Claudia Delgado; Juliet Hermes; Emma Heslop; Cora Hörstmann; Kirsten Isensee; Johannes Karstensen; Arno Lambert; Ana Lara-Lopez; Frank Muller-Karger; et al. (Frontiers in Marine Science, 2021)
The UN Decade of Ocean Science for Sustainable Development (Ocean Decade) challenges marine science to better inform and stimulate social and economic development while conserving marine ecosystems. To achieve these objectives, we must make our diverse methodologies more comparable and interoperable, expanding global participation and foster capacity development in ocean science through a new and coherent approach to best practice development. We present perspectives on this issue gleaned from the ongoing development of the UNESCO Intergovernmental Oceanographic Commission (IOC) Ocean Best Practices System (OBPS). The OBPS is collaborating with individuals and programs around the world to transform the way ocean methodologies are managed, in strong alignment with the outcomes envisioned for the Ocean Decade. However, significant challenges remain, including: (1) the haphazard management of methodologies across their lifecycle, (2) the ambiguous endorsement of what is “best” and when and where one method may be applicable vs. another, and (3) the inconsistent access to methodological knowledge across disciplines and cultures. To help address these challenges, we recommend that sponsors and leaders in ocean science and education promote consistent documentation and convergence of methodologies to: create and improve context-dependent best practices; incorporate contextualized best practices into Ocean Decade Actions; clarify who endorses which method and why; create a global network of complementary ocean practices systems; and ensure broader consistency and flexibility in international capacity development.

Conservation in the face of hybridisation: genome-wide study to evaluate taxonomic delimitation and conservation status of a threatened orchid species - Natascha D. Wagner; Mark A. Clements; Lalita Simpson; Katharina Nargar (Conservation Genetics, 2021)

Bayesian Inverse Transient Analysis for Pipeline Condition Assessment: Parameter Estimation and Uncertainty Quantification - Chi Zhang; Martin F. Lambert; Jinzhe Gong; Aaron C. Zecchin; Angus R. Simpson; Mark L. Stephens (Water Resources Management, 2020)

Subject-Specific Surgical Planning for Hip Replacement: A Novel 2D Graphical Representation of 3D Hip Motion and Prosthetic Impingement Information - Arnab Palit; Richard King; Yolanda Gu; James Pierrepont; David Simpson; Mark A. Williams (Annals of Biomedical Engineering, 2019)

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Structural and sampling uncertainty in observed UK daily precipitation extremes derived from an intercomparison of gridded data sets - Ian R. Simpson; Mark P. McCarthy (International Journal of Climatology, 2019)
This paper compares multiple gridded data sets of daily UK precipitation to evaluate structural uncertainty in our reconstructions of historical rainfall. The data sets compared reflect two different sampling strategies and three different grid interpolation methods. In order to separate the influence of sampling and interpolation uncertainties, one of the data sets (produced by the Met Office) has been recreated using the sampling strategy of stations used in the European (E‐OBS) data set. The results confirm and build upon previous studies showing that relying on a relatively sparse but homogeneous network of stations limits the ability of the resulting data set to reliably estimate extreme rainfall at the daily timescale. It is shown that gridding methods that additionally make use of reference climatological data can avoid systematic bias in both the average and extreme events even when using a relatively sparse network of observations. This is an encouraging result in terms of our potential to reliably extend such data sets further back in time where the availability of digitized data is substantially lower than the more modern era.

SNP genotyping reveals major QTLs for plant architectural traits between A-genome peanut wild species - Ratan Chopra; Charles E. Simpson; Andrew Hillhouse; Paxton Payton; Jyotsna Sharma; Mark D. Burow (Molecular Genetics and Genomics, 2018)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Advanced Backcross Quantitative Trait Loci (QTL) Analysis of Oil Concentration and Oil Quality Traits in Peanut (Arachis hypogaea L.) - Jeffrey N. Wilson; Ratan Chopra; Michael R. Baring; Michael Gomez Selvaraj; Charles E. Simpson; Jennifer Chagoya; Mark D. Burow (Tropical Plant Biology, 2017)

Next-generation transcriptome sequencing, SNP discovery and validation in four market classes of peanut, Arachis hypogaea L. - Ratan Chopra; Gloria Burow; Andrew Farmer; Joann Mudge; Charles E. Simpson; Thea A. Wilkins; Michael R. Baring; Naveen Puppala; Kelly D. Chamberlin; Mark D. Burow (Molecular Genetics and Genomics, 2015)

Cristobalite in the 2011–2012 Cordón Caulle eruption (Chile) - C. Ian Schipper; Jonathan M. Castro; Hugh Tuffen; Fabian B. Wadsworth; Debra Chappell; Andres E. Pantoja; Mark P. Simpson; Eric C. Le Ru (Bulletin of Volcanology, 2015)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Practical considerations for conducting ecotoxicity test methods with manufactured nanomaterials: what have we learnt so far? - Richard D. Handy; Nico van den Brink; Mark Chappell; Martin Mühling; Renata Behra; Maria Dušinská; Peter Simpson; Jukka Ahtiainen; Awadhesh N. Jha; Jennifer Seiter; Anthony Bednar; Alan Kennedy; et al. (Ecotoxicology, 2012)
This review paper reports the consensus of a technical workshop hosted by the European network, NanoImpactNet (NIN). The workshop aimed to review the collective experience of working at the bench with manufactured nanomaterials (MNMs), and to recommend modifications to existing experimental methods and OECD protocols. Current procedures for cleaning glassware are appropriate for most MNMs, although interference with electrodes may occur. Maintaining exposure is more difficult with MNMs compared to conventional chemicals. A metal salt control is recommended for experiments with metallic MNMs that may release free metal ions. Dispersing agents should be avoided, but if they must be used, then natural or synthetic dispersing agents are possible, and dispersion controls essential. Time constraints and technology gaps indicate that full characterisation of test media during ecotoxicity tests is currently not practical. Details of electron microscopy, dark-field microscopy, a range of spectroscopic methods (EDX, XRD, XANES, EXAFS), light scattering techniques (DLS, SLS) and chromatography are discussed. The development of user-friendly software to predict particle behaviour in test media according to DLVO theory is in progress, and simple optical methods are available to estimate the settling behaviour of suspensions during experiments. However, for soil matrices such simple approaches may not be applicable. Alternatively, a Critical Body Residue approach may be taken in which body concentrations in organisms are related to effects, and toxicity thresholds derived. For microbial assays, the cell wall is a formidable barrier to MNMs and end points that rely on the test substance penetrating the cell may be insensitive. Instead assays based on the cell envelope should be developed for MNMs. In algal growth tests, the abiotic factors that promote particle aggregation in the media (e.g. ionic strength) are also important in providing nutrients, and manipulation of the media to control the dispersion may also inhibit growth. Controls to quantify shading effects, and precise details of lighting regimes, shaking or mixing should be reported in algal tests. Photosynthesis may be more sensitive than traditional growth end points for algae and plants. Tests with invertebrates should consider non-chemical toxicity from particle adherence to the organisms. The use of semi-static exposure methods with fish can reduce the logistical issues of waste water disposal and facilitate aspects of animal husbandry relevant to MMNs. There are concerns that the existing bioaccumulation tests are conceptually flawed for MNMs and that new test(s) are required. In vitro testing strategies, as exemplified by genotoxicity assays, can be modified for MNMs, but the risk of false negatives in some assays is highlighted. In conclusion, most protocols will require some modifications and recommendations are made to aid the researcher at the bench.

A 1000‐year record of dry conditions in the eastern Canadian prairies reconstructed from oxygen and carbon isotope measurements on Lake Winnipeg sediment organics - William Mark Buhay; Shawna Simpson; Harvey Thorleifson; Mike Lewis; John King; Alice Telka; Paul Wilkinson; Jeff Babb; Sandra Timsic; Dan Bailey (Journal of Quaternary Science, 2009)
A short sediment core (162 cm), covering the period AD 920–1999, was sampled from the south basin of Lake Winnipeg for a suite of multi‐proxy analyses leading towards a detailed characterisation of the recent millennial lake environment and hydroclimate of southern Manitoba, Canada. Information on the frequency and duration of major dry periods in southern Manitoba, in light of the changes that are likely to occur as a result of an increasingly warming atmosphere, is of specific interest in this study. Intervals of relatively enriched lake sediment cellulose oxygen isotope values ( δ 18 O cellulose ) were found to occur from AD 1180 to 1230 (error range: AD 1104–1231 to 1160–1280), 1610–1640 (error range: AD 1571–1634 to 1603–1662), 1670–1720 (error range: AD 1643–1697 to 1692–1738) and 1750–1780 (error range: AD 1724–1766 to 1756–1794). Regional water balance, inferred from calculated Lake Winnipeg water oxygen isotope values ( δ 18 O inf‐lw ), suggest that the ratio of lake evaporation to catchment input may have been 25–40% higher during these isotopically distinct periods. Associated with the enriched δ 18 O cellulose intervals are some depleted carbon isotope values associated with more abundantly preserved sediment organic matter ( δ 13 C OM ). These suggest reduced microbial oxidation of terrestrially derived organic matter and/or subdued lake productivity during periods of minimised input of nutrients from the catchment area. With reference to other corroborating evidence, it is suggested that the AD 1180–1230, 1610–1640, 1670–1720 and 1750–1780 intervals represent four distinctly drier periods (droughts) in southern Manitoba, Canada. Additionally, lower‐magnitude and duration dry periods may have also occurred from 1320 to 1340 (error range: AD 1257–1363), 1530–1540 (error range: AD 1490–1565 to 1498–1572) and 1570–1580 (error range: AD 1531–1599 to 1539–1606). Copyright © 2009 John Wiley & Sons, Ltd.

What is a Genus in Cypereae: Phylogeny, Character Homology Assessment and Generic Circumscription in Cypereae - A. Muthama Muasya; Alexander Vrijdaghs; David A. Simpson; Mark W. Chase; Paul Goetghebeur; Erik Smets (The Botanical Review, 2009)

Phylogeny of Cyperaceae Based on DNA Sequence Data: Current Progress and Future Prospects - A. Muthama Muasya; David A. Simpson; G. Anthony Verboom; Paul Goetghebeur; Robert F. C. Naczi; Mark W. Chase; Erik Smets (The Botanical Review, 2009)

Uncertainties in the relationship between atmospheric nitrogen deposition and forest carbon sequestration - MARK A. SUTTON; DAVID SIMPSON; PETER E. LEVY; ROGNVALD I. SMITH; STEFAN REIS; MARCEL Van OIJEN; WIM De VRIES (Global Change Biology, 2008)
In a recent study, Magnani et al. report how atmospheric nitrogen deposition drives stand‐lifetime net ecosystem productivity (NEP av ) for midlatitude forests, with an extremely high C to N response (725 kg C kg −1 wet‐deposited N for their European sites). We present here a re‐analysis of these data, which suggests a much smaller C : N response for total N inputs. Accounting for dry, as well as wet N deposition reduces the C : N response to 177 : 1. However, if covariance with intersite climatological differences is accounted for, the actual C : N response in this dataset may be et al. Multisite regression of simulated NEP av vs. total N deposition reproduces a high C : N response (149 : 1). However, once the effects of intersite climatological differences are accounted for, the value is again found to be much smaller, pointing to a real C : N response of about 50–75 : 1.

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

The regulation of virulence in phytopathogenic Erwinia species: quorum sensing, antibiotics and ecological considerations - Neil A. Whitehead; Joseph T. Byers; Paul Commander; Mark J. Corbett; Sarah J. Coulthurst; Lee Everson; Abigail K.P. Harris; Clare L. Pemberton; Natalie J.L. Simpson; Holly Slater; Debra S. Smith; Martin Welch; et al. (Antonie van Leeuwenhoek, 2002)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Rhizogenesis in Forsythia×intermedia and Syringa vulgaris ; application of a simple internode experimental system - T. R. Marks; S. E. Simpson (Plant Cell Reports, 2000)

Interaction of explant type and indole-3-butyric acid during rooting in vitro in a range of difficult and easy-to-root woody plants - Tim R. Marks; Sally E. Simpson (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

An assessment of suprageneric phylogeny inCyperaceae usingrbcL DNA sequences - Abraham M. Muasya; David A. Simpson; Mark W. Chase; Alastair Culham (Plant Systematics and Evolution, 1998)